Pelatihan Ecoprint Berbasis Tumbuhan Lokal: Penguatan Kreativitas dan Minat Kewirausahaan Siswa MIN 1 Soppeng - Harti Oktarina; Irham Maulana Yunus; Muh. Yunus; Ninah Wahyuni A; Sitti Hajar Aswad (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
Creativity, environmental awareness, and an entrepreneurial orientation should be fostered through concrete learning experiences from primary education. This community engagement program aimed to improve students’ ecoprint-making skills, creativity, and entrepreneurial interest through the use of local plants. The training was conducted on 24 November 2025 at MIN 1 Soppeng, South Sulawesi, and involved 20 students in Grades IV–VI. A participatory, learning-by-doing approach was employed, consisting of coordination, an introduction to ecoprint and product value, a pounding-technique demonstration, group practice, and evaluation. Product observation and a 1–4 pre- and post-activity questionnaire were used. The report recap indicates that the mean entrepreneurial-interest score increased from 2.8 to 3.6 (28.6%), while creativity increased from 3.0 to 3.7 (23.3%). Sixteen of the 20 students showed improved entrepreneurial-interest scores. All participants completed the tote-bag production stages and produced varied leaf-based compositions. Ecoprint training may serve as a contextual project integrating art, environmental education, and early entrepreneurship. Program continuity requires teacher mentoring, a standardized product rubric, and evaluation based on documented individual-level data.